Pediatric Vaccination System (I-Vacci) - Shalini, Mariyappan (2012)
Web based pediatrics vaccination system (I-VACCI) is a web based system that is developed to assist health care professional and public health administrator in managing the vaccination for pediatrics. The web based system, I-VACCI, will record vaccination records for Malaysian‟s pediatrics. The concept of a web-based pediatrics vaccination system is, it stores, records and maintains data of vaccination record for Malaysian pediatrics. I-VACCI helps health care professional to manage better vaccination data such as the types of vaccination given to the pediatrics according to the schedule, generate factual data on the progress of immunization in the country and manage better its operation and optimize its cost. I-VACCI is developed by using Hypertext Preprocessor (PHP) and MySQL as the database. PHP is used because it is widely used and powerful language. IVACCI will be accessed via Internet. Finally, we can conclude that the web based pediatrics vaccination system (I-VACCI) will be an advantage to manage the vaccination that given to the pediatrics and it benefits to various parties.